Increased obesity rate due to economic transition and industrialisation in Asia: a systematic review - Goh, Wu-Dong-Yan; Chong, Li-Choo; Kuan, Yau-Hoong; Mohamed Noor Mohamed Ismail (Penerbit Universiti Kebangsaan Malaysia, 2020)
Owing to economic transition and urbanisation, nutrition problems in Asia have shifted from malnutrition to over-nutrition. As a result, the obesity rate in Asia is rising at an alarming rate. This review aims to provide an overview of the key factors and current strategies of this phenomenon in Asia from the socio-economic point of view as well as to provide insights of possible ways to overcome these issues by analysing works of literature published between 2000 and 2018. Diet-related factors such as energy intake surplus, overconsumption of processed food, fat and sugar are among the largest contributors to this epidemic. The underlying factor of the surplus of energy intake was due to socioeconomic and cultural factors such as improved purchasing power and deep-rooted cultural associations of obesity with prosperity. Efforts have been put in by governments, NGOs, and the food industry to cope with obesity. These include the implementation of dietary guidelines, organisation of public health campaigns, enforcement of nutrition labelling on food products, application of fiscal policy, and marketing ban of energy-dense nutrient-poor (EDNP) food products to children. However, these collective efforts have not been effective. Therefore, authorities should seek long term alternative ways such as food reformulation and ‘food zoning’ to create a conducive environment that encourages a healthy diet.